The relations between delay in diagnosis in the case of patienss Pulmonary Tuberculosis with distance from home and employment of patients in Health Reference Fascility (BBKPM) Surakarta - LES YASIN; Reviono .; Riza Novierta (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2016)
Background : Tuberculosis (TB) is the second major leading cause of death worldwide due to infectious diseases, with the incidence and prevalence of cases is still high in some countries in the world, and Indonesia is included. Early diagnosis is the key of the program to control the new cases of pulmonary TB. Delays in diagnosis of pulmonary tuberculosis patients remains a problem that is caused by many factors including the distance from home and employment status as the risk factor. This study aims to determine the relationship between delay in diagnosis in the case of patients pulmonary TB with a distance from home and employment status in BBKPM Surakarta. Methods This study was observational analytic study approach cross-sectional are held on October to December 2015 in Balai Besar Kesehatan Paru Masyarakat (BBKPM) Surakarta.Total of 66 subjects were selected by consecutive sampling method. New cases of pulmonary TB patients in BBKPM Surakarta was collected by direct interview and using questionare about the delay, distance from home and employment status. Data was analyzed by using multiple chi-square models and processed with Statistical Product and Service Solutions (SPSS) 20.00 for Windows. Results: The total 66 samples, obtained samples with 45 people working status and the samples do not work amounted to 21 people. Samples with that far distance from home as many as 38 people and the sample of distance closely from home to medical care as many as 28 people. Samples were late with number 34 and do not experience delays amount to 32 people. Distance from home much influence on the occurrence of patient delay. Patients with far distance from home visiting for the first time to a health facility more slower than those with distance closely from home (p = 0,808). Effect on the employment status of the patients delay. Patient with status working visit for the first time to health facilities more slower than the patients with status do not work (p = 0,297). Conclusion: There is a moderate correlation between the delay in diagnosis in the cases of patients pulmonary Tuberculosis with distance from home and employment of Patients in BBKPM Surakarta, but the result were not statistically significant. Keywords: distance from home, employment status, the patient delays